Tarihi Yapıların Yeniden Kullanılmasında Yapı-İşlev Uyumu: Rize Müzesi Örneği / The Structure-Function Coherence in the Reuse of Historical Buildings: Rize Museum Sample - İslamoğlu, Özge (Journal of History Culture and Art Research, 2018)
Abstract The reuse of historic buildings for the purpose of protection is an important tool in the preservation of the historic buildings. With this understanding of protection, the building continues its life and, at the same time, economic and cultural continuity is ensured. In this study, Sarı Ev which have been refunctioned today and known as Rize Museum, reflecting architectural texture of Eastern Black Sea and representing the architectural heritage of the city, has been evaluated in the context of reutilization. The aim of the study is to draw attention to the importance of function selection in reuse by showing this structure, which originally used to function as a house, that can be compatible with the new function. The aim of the study is to draw attention to the importance of function selection in reuse by showing this structure, which originally used to function as a house, that can be compatible with the new function. The suitability of the structure considering its spatial and functional requirements for reuse has been assessed. The adaptation of the building to its new function was examined by the observation and spatial analysis method and evaluated qualitatively. The result of the evaluation showed that the original spatial installations of the construction were adaptable to the new function with very little intervention. In this study, a positive example of the proper function selection for the reuse of construction has been presented and emphasized as an important way for preservation in the face of rapidly changing circumstances of present conditions. Öz Tarihi yapıların koruma amaçlı olarak yeniden kullanımı, yapıların sahip olduğu değerlerin korunmasında önemli bir araçtır. Değerlerin yaşatıldığı bu koruma anlayışı ile yapı yaşamına devam etmekte, aynı zamanda ekonomik ve kültürel açıdan süreklilik sağlanmaktadır. Bu çalışmada, Doğu Karadeniz’in mimari dokusunu yansıtan ve kentin mimari mirasları arasında yer alan Sarı Ev incelenmiş ve Rize müzesi olarak yeniden kullanıma açılması ile ilgili değerlendirmeler yapılmıştır. Çalışmanın amacı özgün işlevi konut olan bu yapının yeni işlev ile uyumunun ortaya koymak ve yeniden kullanımda işlev seçiminin önemine dikkat çekmektir. Bunun için yapının yeniden kullanımındaki mekânsal ve işlevsel gereksinimlerine uygunluğu değerlendirilmiştir. Yapının yeni işleve olan uyumu, yapılan gözlem ve mekânsal analiz yöntemiyle sorgulanmış, niteliksel açıdan bir değerlendirme yapılmıştır. Yapılan değerlendirme sonucu, yapının özgün mekânsal kurgularının değişime uğramadan, çok az müdahale ile yeni işleve uyum sağladığını göstermiştir. Yeniden kullanımda yapıya uygun işlev seçiminin olumlu bir örneğinin ortaya konulduğu çalışmada, bu yöntemin günümüz koşullarında hızla değişen koşullar karşısında korumada izlenebilecek önemli bir yol olduğu vurgulanmaktadır.